Loxosceles spider bites in the state of Paraná, Brazil: 1993-2000 - Marques-da-Silva,E. (2006)
This study presents the epidemiological analysis of 20,699 reported spider bites involving the Loxosceles genus in the state of Paraná, Brazil, from 1993 to 2000. The incidence rate in the period was 290.24/100,000 inhabitants. The results show that 95.04% of the accidents occurred in two Health Regions of the state: greater metropolitan Curitiba (92.9%) and Irati (2.14%). The major incidence was recorded in greater metropolitan Curitiba (559.1/100,000). Loxosceles bites were more frequent in females (61%) than in males. Antivenin therapy was not necessary in 95.4% (19,662) of the cases. From the cases in which information about the time elapsed between the bite and medical treatment was recorded (9,679), 31.8% received treatment from 6 to 48 hours after the bite. Among the cases with severity rate recorded (12,096), 2.1% were severe, 50.4% moderate, and 47.4% mild. Seven deaths from Loxosceles bites were recorded, corresponding to a fatality rate of 0.03%.